The Qur'an Learning Strategy in Raudhatul Jannah Majelis Taklim, Kapuk, West Jakarta - Fatimah Azzahro; Hartini Salama (LP2M STIT Palapa Nusantara, 2024)
Majelis Taklim is a non-formal Islamic educational institution. The primary focus of study in Majelis Taklim is the learning of the Qur’an. Therefore, it is essential to understand effective Qur’anic learning strategies used in Majelis Taklim. This research aims to identify Qur’anic learning strategies. The study employs a descriptive qualitative method with purposive sampling data collection techniques. The subject of this research is the Raudhatul Jannah Majelis Taklim in Cengkareng, Kapuk, West Jakarta. The research instruments used include observation and interviews. The data were analyzed using the interactive model of Miles and Huberman, along with the Kaif learning strategy. The findings reveal that MT RJ employs direct learning strategies in Qur’anic instruction. Qur’anic learning at MT RJ focuses on both reading skills and Qur’anic knowledge. The development of Qur’anic reading skills is conducted using the Talaqqi method and the Jama’ model. Meanwhile, Qur’anic knowledge instruction uses the bi al-hikmah method and mau’izah (lecture and discussion) through the Tafahum learning model. Based on observations and interviews, the development of Qur’anic learning strategies at MT RJ is found to be effective.